Estrategias de aprendizaje microlearning como fundamento para el diseño de actividades en entornos virtuales de aprendizaje del area de matematicas en la Unidad Educativa Carlos Cisneros. - Ayavaca Vallejo, Bolivar Leonardo (2022)
ABSTRACT Microlearning strategies permit the student to obtain significant learning, and the teacher uses technological strategies in the classroom to understand a specific topic. The importance of this study lies in the fact that the teacher acquires new teaching strategies, encouraging him to innovate his methodology based on technology and obtain a better understanding of the students in the issues that are complex for them. This research aims to determine the incidence of using microlearning strategies through virtual environments in learning arithmetic operations in 4th- grade students of the Carlos Cisneros Educational Unit. The research has a quasi-experimental design. The study began with a test of the four arithmetic operations, addition, subtraction, multiplication, and division, taught using a traditional method. The students were separated into three groups. Each group applied each arithmetic operation's microlearning strategies of repetition, elaboration, and organization, culminating with a test after each application. It was evidenced that the strategies that provide better meaningful learning to the students in the operations of addition, subtraction, and division are that of organization, while in multiplication, it is that of elaboration. Keywords: Microlearning, learning strategies, arithmetic operations. Firmado electrónicamente por: LORENA DEL PILAR SOLIS VITERI Reviewed by: Mgs. Lorena Solis Viteri ENGLISH PROFESSOR c.c. 0603356783